The Ukrainian ethnic borders in the Black Sea region in the 1920-1930s Ukrainian social and political thought - Казанков, Роман (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
The article deals with the features of the Black Sea region’s image in the Ukrainian inter-war emigration’s socio-political works. Has been highlighted the efforts of the institutional study of the region by creating a Ukrainian Black Sea Institute. Close attention has been given to the S. Rudnytsky and Ju. Lypa works which had a significant impact on the understanding of the Black Sea region by the next generations of Ukrainian diaspora.